UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN IMPROVING PARENTAL INVOLVEMENT IN CHILDREN'S EDUCATION - Firmansyah Firmansyah; Ferianto; Syarifuddin (CV. Adiba Aisha Amira, 2024)
In the last two decades, Information and Communication Technology (ICT) has transformed the education landscape, opening up new opportunities to increase parental involvement in children's education. This study aims to explore how ICT can be used to support parental involvement in children's learning and identify possible challenges and strategies to overcome them. The study was conducted through a comprehensive literature review, collecting and analyzing data from various sources, including peer-reviewed journals, academic conferences, research reports and case studies relevant to the use of ICT in education. The results of the literature show that ICT plays an important role in enhancing parental engagement through communication tools such as email, parent portals, and mobile applications that enable access to educational information and communication between school and home. It was found that enhanced parental involvement through ICT contributes to increased student learning motivation and better educational outcomes. However, challenges such as technology access gaps, lack of digital literacy skills among parents, and privacy and data security concerns were also revealed. Strategies to address these challenges include increased investment in ICT infrastructure, digital literacy training programs for parents, and implementation of strong privacy and security policies.